2008
DOI: 10.1111/j.1747-0285.2008.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of AM1 and B3LYP‐DFT for Inhibition of MAO‐A by Phenylisopropylamines: A QSAR Study

Abstract: The aim of this study is to provide an initial indication regarding the scope and limitations of some state-of-the-art methods in computational chemistry, including semiempirical (AM1) and density functional theory (B3LYP), in the flip regression procedure applied to the inhibition of phenylisopropylamines. The results show that the models established based on the density functional theory-B3LYP are better than that based on semiempirical method (AM1). It is demonstrated that electron-rich ring systems and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Thus, the lowest energy non-redundant conformers of a ligand were used for pharmacophore model development. [16] A couple of conformer was defined as identical if the relative distance between them is below 1.00 Å. [17]…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the lowest energy non-redundant conformers of a ligand were used for pharmacophore model development. [16] A couple of conformer was defined as identical if the relative distance between them is below 1.00 Å. [17]…”
Section: Methodsmentioning
confidence: 99%
“…A previous study carried out in phenylalkylamines also revealed that electronic descriptors had an important contribution in the development of the QSAR model [83]. Deeb et al [101] further studied a set of phenylisopropylamines through semiempirical (AM1) and density functional theory (DFT) calculations [102]. They showed that the orientation of nodes and the energies of the occupied π orbitals have a powerful explanatory contribution to the variance in the MAO-A activity.…”
Section: Prediction Of Mao Activity Through 3d Ligand-based Modelsmentioning
confidence: 99%
“…Full geometric optimizations were performed for all structures by the DFT method with the hybrid functional B3LYP (Becke's three‐parameter function using the Lee, Yang, and Parr correlation function)31, 32 at the 6‐311+G(d,p) theoretical level. Previous studies28, 29, 33–44 have demonstrated the DFT‐B3LYP method to be appropriate for the investigation of the structure‐property relationships of carcinogens and drugs. Because the biomolecular damage in vivo induced by CCNU derivatives took place in aqueous solution, the solvent effect of water was taken into account.…”
Section: Models and Computationsmentioning
confidence: 99%